2010
DOI: 10.1371/journal.pone.0012702
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Heparin-Binding EGF-Like Growth Factor by miR-212 and Acquired Cetuximab-Resistance in Head and Neck Squamous Cell Carcinoma

Abstract: BackgroundWe hypothesized that chronic inhibition of epidermal growth factor receptor (EGFR) by cetuximab, a monoclonal anti-EGFR antibody, induces up-regulation of its ligands resulting in resistance and that microRNAs (miRs) play an important role in the ligand regulation in head and neck squamous cell carcinoma (HNSCC).Methodology/Principal FindingsGenome-wide changes in gene and miR expression were determined in cetuximab-sensitive cell line, SCC1, and its resistant derivative 1Cc8 using DNA microarrays an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 47 publications
5
116
0
2
Order By: Relevance
“…1). Our comprehensive analysis of how both low-and high-affinity EGFR ligands and ligand mixtures impact monoclonal antibody antagonism confirms and extends prior work with single ligands and cetuximab (19)(20)(21).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…1). Our comprehensive analysis of how both low-and high-affinity EGFR ligands and ligand mixtures impact monoclonal antibody antagonism confirms and extends prior work with single ligands and cetuximab (19)(20)(21).…”
Section: Discussionsupporting
confidence: 80%
“…For example, preclinical studies show that upregulation of TGFa or HB-EGF can maintain EGFR signaling and promote cetuximab resistance (19)(20)(21), whereas heregulin and hepatocyte growth factor can induce cetuximab resistance via bypass of EGFR (22,23). In contrast, AREG upregulation correlates with sensitivity to cetuximab and EGFR TKIs in vitro (24,25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-clinical data suggested that inhibition of EGFR, HER2, and HER3 by combined treatment with lapatinib, trastuzumab and U3-1287 showed maximum effect in trastuzumab-resistant HER2-overexpressing breast cancer ( Figure 5A). It has been exhibited that cetuximab-resistant clones have increased not only EGFR, HER2, HER3, and HER4, but also other receptor tyrosine kinases (RTKs) such as cMET, AXL, and IGF1R (13,45,46). Recently, mutations in the genes encoding other RTKs, such as FGFR1 or PDGFRA were found in CRC PDX models with intrinsic resistance to cetuximab (47).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of an expression dataset of cetuximabsensitive and cetuximab-resistant HNSCC cell lines showed that PTPRS expression was significantly lower in resistant cells (P = 6 × 10 −4 ) (Fig. 4C) (48). Unfortunately, expression datasets from patients with tyrosine kinase inhibitor (TKI)-sensitive and -resistant HNSCC and lung tumors are not currently available for our analysis.…”
Section: Protein Tyrosine Phosphatase Receptor S (Ptprs) Is Frequentlymentioning
confidence: 99%